2006
DOI: 10.1111/j.1540-627x.2006.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Family Firms and Corporate Governance*

Abstract: This paper contributes to the agency theory literature by identifying relations between family control and corporate governance structure. Emerging literature supports the notion that family control creates strong incentives that have potentially competing influences on the manner in, and extent to, which internal corporate governance mechanisms are utilized. A sample of 100 listed companies (evenly divided between family and nonfamily firms) is used to test the hypotheses that corporate governance structures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
111
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(131 citation statements)
references
References 33 publications
7
111
0
4
Order By: Relevance
“…Some of them relied on majority ownership (50% or more) as a threshold to determine a family business, arguing that the majority of ownership is indicative of majority in decision-making rights as well (Classen et al, 2014;Vandekerkhof et al, 2015). Others, however, have used a much lower ownership threshold, such as 25% (Kraiczy, Hack and Kellermanns, 2014;Leitterstorf and Rau, 2014), 20% (Bartholomeusz and Tanewski, 2006), 15% (Denison, Lief and Ward, 2004) or even as low as 5% (Strike et al, 2015).…”
Section: Family Business Operational Definitionmentioning
confidence: 99%
“…Some of them relied on majority ownership (50% or more) as a threshold to determine a family business, arguing that the majority of ownership is indicative of majority in decision-making rights as well (Classen et al, 2014;Vandekerkhof et al, 2015). Others, however, have used a much lower ownership threshold, such as 25% (Kraiczy, Hack and Kellermanns, 2014;Leitterstorf and Rau, 2014), 20% (Bartholomeusz and Tanewski, 2006), 15% (Denison, Lief and Ward, 2004) or even as low as 5% (Strike et al, 2015).…”
Section: Family Business Operational Definitionmentioning
confidence: 99%
“…Moreover, the family-owners view the company as the capital and assets transfer to the next generation (Bartholomeusz and Tanewski, 2006). Hence, they aim to maximize the firm value and profitability.…”
Section: Effects Of Family-controlled Company On Company Performancementioning
confidence: 99%
“…Some researches indicate that CG can mitigate the agency threats in family-controlled business through monitoring the controlling shareholders and disclosure requirements, and enhancing company performance (Schulze, 2001;Ho, 2003;Bartholomeusz and Tanewski, 2006;Braun and Sharma, 2007).…”
Section: Effects Of Family-controlled Company On Company Performancementioning
confidence: 99%
“…However research done on SMME family firms can be made applicable to this study as most SMMEs are family owned businesses and have all the applicable characteristics of SMMEs. Bartholomeusz and Tanewski (2006), conducted research on 100 listed companies (evenly divided between family and non-family companies) and found that family owned organisations had a closer locus of control with little opportunity for external involvement. The practical implications of these findings according to them are that these family organisations should implement more transparent corporate governance structures and be subject to greater discipline from independent bodies.…”
Section: Literature Review On Succession Planningmentioning
confidence: 99%
“…The practical implications of these findings according to them are that these family organisations should implement more transparent corporate governance structures and be subject to greater discipline from independent bodies. This then will maximize the company's value (Bartholomeusz and Tanewski, 2006). Bocatto, Gispert & Rialp (2010), investigated 86 nonfinancial firms listed on the Spanish Stock Exchange, to observe how their pre-performance influenced the nomination of a family or a non-family member to top senior positions.…”
Section: Literature Review On Succession Planningmentioning
confidence: 99%